FACTORS AFFECTING EFFECTIVE IMPLEMENTATION OF WIND POWER PROJECTS IN KENYA - Ali, Abdullahi Gira; Kiarie, Dr. Mburu David (International Journal of Entrepreneurship and Project Management, 2017)
Purpose: The purpose of this study was to determine factors affecting effective implementation of wind power projects in Kenya Methodology: The study adopted descriptive survey research design. The target population for the study was 128 stakeholders. The study used a 10% pretest sample which was given sample of 13 respondents which were randomly selected from the projects' stakeholders. Stratified random sampling was used to select the respondents. The unit of observation in this study was community leaders, donors, project managers and government agents. The study used primary data gathered by use of a structured and semi-structured questionnaire. The questionnaires were self-administered using a drop and pick method. This involved a pilot study being undertaken on 10% (13) of the stakeholders to test the reliability and validity of the questionnaire. The completed questionnaires were analyzed for consistency and then coded. The coded questionnaires were then analyzed using computer software and preferably the Statistical Packages for Social Science and percentages and inferential statistics (Pearson Product Moment Correlation Coefficients and multiple regression coefficients). Results: The study findings revealed that community involvement, top management support, donor funding and government regulations positively and significantly affects effective implementation of wind power projects in Kenya. Policy recommendation: The study recommends that governments through regulations should ensure that there is adequate monitoring throughout the entire implementation period to prevent any un necessary and/or avoidable delays or disruptions to implementation schedules further other studies could consider study on other renewable energy for the purpose of making a comparison of the findings with those of the current study.